2019
DOI: 10.3329/bhj.v34i2.44443
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exercise Tolerance Test in the Screening of Suspected Myocardial Ischemia in Bangladeshi Patients

Abstract: Background: Ischemic Heart Disease (IHD) is preventable and reversible if early screening and elimination of the risk factors like life style modification and dietary intervention can be done. Exercise Tolerant Test (ETT) has become an important diagnostic tool to evaluate patient with suspected or known case of ischemic heart disease. Objective: To determine the frequency of IHD among subjects who presented with chest pain and to identify the common indications for ETT. Methodology: It was a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We evaluated the angiography results of 94 consecutive patients who were enrolled after they were labeled positive for inducible angina on ETT via the Bruce protocol. The literature regards ETT as an initial measure to assess and rule out myocardial ischemia [ 2 , 3 , 11 ]. The overall sensitivity of this inexpensive test is reported to be as high as 98%; however, its specificity is quite low [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated the angiography results of 94 consecutive patients who were enrolled after they were labeled positive for inducible angina on ETT via the Bruce protocol. The literature regards ETT as an initial measure to assess and rule out myocardial ischemia [ 2 , 3 , 11 ]. The overall sensitivity of this inexpensive test is reported to be as high as 98%; however, its specificity is quite low [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall sensitivity of this inexpensive test is reported to be as high as 98%; however, its specificity is quite low [ 5 ]. Studies have reported that low specificity can be attributed to a myriad of contributing parameters including metabolic diseases, structural heart diseases, conduction disturbances, and digitalis therapy [ 3 , 5 ]. In developing countries, further evaluation in patients with coronary artery disease hinges upon the results of ETT, a relatively inexpensive and easy to interpret test [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations